Saying All That Can Be Said : The Art of Describing Sex in Jin Ping Mei - McMahon, Keith, (Harvard University Asia Center, 2023)
In Saying All That Can Be Said , Keith McMahon presents the first full analysis of the sexually explicit portrayals in the Ming novel Jin Ping Mei 金瓶梅 (The Plum in the Golden Vase). Countering common views of those portrayals as "just sex" or as "bad sex," he shows that they are rich in thematic meaning and loaded with social and aesthetic purpose. McMahon places the novel in the historical context of Chinese sexual culture, from which Jin Ping Mei inherits the style of the elegant, metaphorical description of erotic pleasure, but which the anonymous author extends in an exploration of the explicit, the obscene, and the graphic. The novel uses explicit description to evaluate and comment on characters, situations, and sexual and psychic states of being. Echoing the novel's way of taking sex as a vehicle for reading the world, McMahon celebrates the richness and exuberance of Jin Ping Mei's language of sex, which refuses imprisonment within the boundaries of orthodox culture's cleanly authoritative style, and which continues to inspire admiration from readers around the world. Saying All That Can Be Said will change the way we think about sexual culture in premodern China. See Less